2012
DOI: 10.1016/j.molcel.2012.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Modularity and the Evolution of Genetic Interactomes across Species

Abstract: To date, cross-species comparisons of genetic interactomes have been restricted to small or functionally related gene sets, limiting our ability to infer evolutionary trends. To facilitate a more comprehensive analysis, we constructed a genome-scale epistasis map (E-MAP) for the fission yeast Schizosaccharomyces pombe, providing phenotypic signatures for ~60% of the non-essential genome. Using these signatures, we generated a catalogue of 297 functional modules, and assigned function to 144 previously uncharac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
249
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 192 publications
(281 citation statements)
references
References 82 publications
29
249
0
3
Order By: Relevance
“…1B) (45). In addition, comparisons of genetic interactions between S. pombe and S. cerevisiae suggested that these four proteins form a complex, and we confirmed this biochemically (40). Collectively, these data demonstrate that Tul1, Dsc2, Dsc3, and Ubx3 are subunits of the Tul1 E3 ligase in S. cerevisiae that is homologous to the S. pombe Dsc E3 ligase.…”
Section: Methodssupporting
confidence: 79%
See 3 more Smart Citations
“…1B) (45). In addition, comparisons of genetic interactions between S. pombe and S. cerevisiae suggested that these four proteins form a complex, and we confirmed this biochemically (40). Collectively, these data demonstrate that Tul1, Dsc2, Dsc3, and Ubx3 are subunits of the Tul1 E3 ligase in S. cerevisiae that is homologous to the S. pombe Dsc E3 ligase.…”
Section: Methodssupporting
confidence: 79%
“…Given that Tul1 ubiquitylates Pep12D to target it to the vacuole (13), DSC2, DSC3, and UBX3 are also likely required for Tul1 E3 ligase activity. Finally, published genetic interaction data indicate that these four genes function in the same pathway (40,45).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this regard, we find that disruption of the telomeric association of arm regions in sap1-1 cells lacking Shelterin components correlates with increased accumulation of DNA damage. Moreover, certain Shelterin components show negative genetic interactions with DNA repair and checkpoint factors (44).…”
Section: Discussionmentioning
confidence: 99%